FACE-SAVING AND FACE-THREATENING NEGOTIATION BY LECTURERS: GENDER AND TEACHING EXPERIENCE DIFFERENCES - Sheila Agustina (Universitas Islam Sumatera Utara (UISU), 2021)
Teachers’ use of language was believed to give impact for the success of language learners in one way or another. As some teachers’ speech included managing classroom, giving instructions, and providing feedbacks, it is inevitable that a teacher would use the power and make the students uncomfortable. To soften the speech or lessen the impact to the students, a teacher could use some strategies of politeness inside the classroom. Seeing how linguistic politeness manifested by teachers could generally affect the students’ esteem, this study aimed at observing face-threatening and face-saving utterances produced by six lecturers during 6 different lessons in a state university. Combining Brown and Levinson’s theory of politeness and Yule’s concept of face, this study would also contrast the language production by lecturers of different gender and different length of teaching experience to find out if they were correlated. Under the qualitative method, the researcher carried out class observation, recorded the interaction, and transcribed all of the lecturers’ utterances. This study revealed that lecturers generally tend to manage more face-saving acts. However, it showed that most face-threatening utterances were generated by male lecturers. It also indicated that lecturers with longer teaching experience produced more face-threatening utterances, and lecturers with shorter teaching experience produced more face-saving utterances. The fact that female lecturers in this study were dominant in negotiating face-saving acts justified women are more polite than men.